Administrasi Perpustakaan Di Perguruan Tinggi - Usman Usman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Library serves as a center of learning activities, information center, a research center in order to obtain a reading science, and recreation areas need to be developed and be expanded so that consumers can take advantage of the library as a source of effective learning. But reality shows that the role and function of the library is often overlooked by everyone. Writing this leads to aspects of management and governance activities in the college library. The benefits derived from this paper is expected to add to the information, insights, ideas, and knowledge in the administrative review of the library, a reference in developing libraries in educational institutions and government agencies, improve library management system in a professional manner so as to provide access to the information required in accordance with the requirements academics and community needs. Abstrak Perpustakaan berfungsi sebagai pusat kegiatan belajar mengajar, pusat informasi, tempat penelitian, pusat membaca guna memperoleh ilmu, dan tempat rekreasi perlu dibina dan dikembangan sehingga konsumen dapat memanfaatkan perpustakaan sebagai sumber belajar yang efektif. Namun realitas menunjukkan bahwa peran dan fungsi perpustakaan sering terabaikan oleh setiap orang. Penulisan ini mengarah pada aspek manajemen dan tata kelola aktivitas di perpustakaan di perguruan tinggi. Manfaat yang diperoleh dari penulisan ini diharapkan dapat menambah informasi, wawasan, pemikiran, dan pengetahuan dalam tinjauan administrasi perpustakaan, menjadi acuan dalam mengembangkan perpustakaan di instansi pendidikan dan instansi pemerintah, meningkatkan sistem pengelolaan perpustakaan secara profesional sehingga mampu memberikan akses informasi yang diperlukan sesuai dengan kebutuhan civitas akademika dan kebutuhan masyarakat. Kata Kunci: Administrasi, Perpustakaan